Heterogeneity in Center Practices in Liver Transplantation for Alcohol-Associated Liver Disease in the United States. (1st September 2022) - Lim, Nicholas; Kwong, Allison J.; Jafri, Syed-Mohammed; Jesse, Michelle T.; Kriss, Michael; Nair, Kavitha; Pillai, Anjana; Shingina, Alexandra; Tang, Qing; Desai, Archita P.
Abstract : INTRODUCTION: Alcohol-related liver disease (ALD) is now the leading indication for liver transplantation (LT) in the United States (US). It remains unclear how centers are managing the medical and psychosocial issues associated with these patients. METHODS: We conducted a web-based survey of LT centers in the United States to identify center-level details on peri-LT management of ALD and related issues. RESULTS: Of the 117 adult LT centers, 100 responses (85.5%) were collected, representing all Organ Procurement and Transplantation Network regions. For alcohol-associated cirrhosis, 70.0% of the centers reported no minimum sobriety requirement while 21.0% required 6 months of sobriety. LT for severe alcohol-associated hepatitis was performed at 85.0% of the centers. Monitoring protocols for pre-LT and post-LT alcohol use varied among centers. DISCUSSION: Our findings highlight a change in center attitudes toward LT for ALD, particularly for severe alcohol-associated hepatitis.